The room can you really trust anyone? - Milicevic, Mladen 1958- (WISEAU-FILMS, 2016)
"Johnny is a successful banker who lives happily in a San Francisco townhouse with his fiancée, Lisa. One day, inexplicably, she gets bored with him and decides to seduce his best friend, Mark. From there, nothing will be the same again." [imdb.com]
Original: USA 2003
Bildformat 1.78:1 (anamorphic widescreen)
Special features: trailer ; scene selection ; deleted scenes ; interview with Tommy Wiseau ; behind the scenes ; still photo gallery
Keywords: Film; DVD-Video